Mainstreaming precision nutrient management practices by national and state governments of India towards food security and climate change mitigation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The central government and state governments of India promote an integrated nutrient management approach (tested and evaluated by CCAFS and National Partners) with potential area coverage of over 10 million hectares benefiting 4 million farmers. This intervention increases nutrient-use-efficiency by 25% which would lead to reduced fertilizer consumption and saving of fertilizer subsidy worth $4 billion annually. This will translate into ca. 3.4 million tonne of CO2 emission reduction per annum with a cost saving of 100 USD/tonne CO2 abated.